Optimization Design of Cementitious Materials Based on Molybdenum Tailings-Desulfurization Gypsum-Calcium Carbide Sludge - Guo, Ziru; Li, Haijie; Chen, Shiying (International Journal of Materials Science and Technology Studies, 2025)
This study developed a composite cementitious material using molybdenum tailings, desulfurization gypsum, and carbide slag as the primary raw materials. The appropriate dosage range of each component was first determined through single-factor experiments. The mix proportion was then optimized using an orthogonal experimental design, and a strength prediction model was established via response surface methodology. The microstructure and hydration mechanism were further investigated by XRD and SEM. The results indicate that the optimal mix ratio is molybdenum tailings: desulfurization gypsum: carbide slag = 29.66 g: 35.45 g: 45 g, with a water-to-binder ratio of 0.402. The 28-day compressive strength of the prepared cementitious material reached 5.59 MPa. The main hydration products were ettringite (AFt) and C-S-H gel, which interweave to form a dense microstructure. This system demonstrates a high-value approach to recycling solid waste and offers a sustainable strategy for producing eco-friendly cementitious materials.